28th AIAA/CEAS Aeroacoustics 2022 Conference 2022
DOI: 10.2514/6.2022-3095
|View full text |Cite
|
Sign up to set email alerts
|

The effect of angle of attack on turbulence interaction noise with a porous leading edge

Abstract: The paper is concerned with the effect of angle of attack on the interaction noise between a turbulent flow and a NACA 0012 airfoil. This experimental study considers an airfoil with a porous leading edge up to 10% of the chord and compares the noise levels to a solid airfoil leading edge at a Reynolds number of ๐‘…๐‘’ = 2.5 ร— 10 5 . Turbulence is generated by the means of a passive grid and the direct noise measurements are performed using a microphone array. The airfoil is instrumented for both steady and unst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…The pressure coefficient results for this configuration are omitted as they are previously reported. 23,24,43 The surface pressure taps were connected in a remote sensing configuration using Panasonic WM-61A microphones, which have a reliable frequency range between 10 < f < 6000 Hz. 47,48 The Panasonic WM-61A microphones measure the pressure fluctuations at the pressure tap via a brass tube which is connected to the microphone in a custom-made holder that is acoustically terminated.…”
Section: A Wind Tunnel and Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The pressure coefficient results for this configuration are omitted as they are previously reported. 23,24,43 The surface pressure taps were connected in a remote sensing configuration using Panasonic WM-61A microphones, which have a reliable frequency range between 10 < f < 6000 Hz. 47,48 The Panasonic WM-61A microphones measure the pressure fluctuations at the pressure tap via a brass tube which is connected to the microphone in a custom-made holder that is acoustically terminated.…”
Section: A Wind Tunnel and Modelmentioning
confidence: 99%
“…The chordwise size of the porous leading edge on the airfoil was selected through the previous study which demonstrated that 10% of the chord was the optimum length of chord that maximized noise reduction, while minimizing the amount of chord that would be occupied by the porous structure. 24 Three leading edges of different porous structures were selected to study the effect of the bulk porous structure on the reduction of airfoil turbulence interaction noise. The three selected structures were of the triply periodic minimal surface (TPMS) family, namely, Schwarz-P, diamond, and gyroid (Fig.…”
Section: Porous Leading Edgesmentioning
confidence: 99%
See 1 more Smart Citation
“…Turbulence interaction is among some of the most important noise generation mechanisms due to its relevance and diversity of engineering applications and it arises from the turbulence distortion and scattering as it impinges on the solid body [4] . There have been numerous experimental studies on turbulence-interaction noise of airfoils and bluff bodies [5][6][7][8][9][10][11][12] and their noise mitigation strategies [13][14][15][16][17][18]. To this day, the experimental production of turbulence upstream of a solid body is being achieved with grids installed within the wind-tunnel nozzle contractions [19,20] and have been extensively used to produce turbulent inflows since the work of Simmons and Salter [21], producing a large number of aerodynamic and aeroacoustic measurements [22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%